The Tobacco Tax And Health Protection Act Of 1988 (Tufts Archival Research Center, 2007)
Text of California's Tobacco Tax and Health Protection Act of 1988. Increases tax on tobacco products in order to reduce smoking prevalence, support medical research, and recoup some social costs of smoking.